Chapter Central occupations: stills from a city in movement - Stevens, Jeroen (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
This visual essay dwells on the particular struggle for the historical city center of São Paulo enacted by contemporary urban occupation movements. The series of photographs, taken during multiple periods of ethnographic fieldwork (2014-2019), seeks to shed light on the notorious bodily encounter between thousands of homeless families engaged in urban movements on the one hand, and the vacated architecture of the city on the other hand. The aim is to interrogate how occupations are particular momentary spaces where the city is brought into motion by urban movements, prefiguring more just and sustainable ways of re-inhabiting, remaking, and rethinking the city.